2011
DOI: 10.1016/j.physletb.2011.08.076
|View full text |Cite
|
Sign up to set email alerts
|

A study of generalized second law of thermodynamics in magnetic universe in the light of non-linear electrodynamics

Abstract: In this work, we have considered the magnetic universe in non-linear electrodynamics. The Einstein's field equations for non-flat FRW model have been considered when the universe is filled with the matter and magnetic field only. We have discussed the validity of the generalized second law of thermodynamics of the magntic universe bounded by Hubble, apparent, particle and event horizons using Gibb's law and the first law of thermodynamics for interacting and non-interacting scenarios. It has been shown that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…. When n = 2 (i.e., for 4D), we can recover the result of Ref Bandyopadhyay et al (2011) (i.e., B ∝ a −2 ) and also when δ = 0, n = 2 and we drop the matter density term (i.e., ρ m = 0), then we can verify the result of Ref. Camara et al (2004) forΛ = 0.…”
supporting
confidence: 86%
“…. When n = 2 (i.e., for 4D), we can recover the result of Ref Bandyopadhyay et al (2011) (i.e., B ∝ a −2 ) and also when δ = 0, n = 2 and we drop the matter density term (i.e., ρ m = 0), then we can verify the result of Ref. Camara et al (2004) forΛ = 0.…”
supporting
confidence: 86%
“…We do not consider the term F F * involving F * in order to preserve the parity [25,26]. The linear term of this Lagrangian dominates during a radiation dominated era, while the quadratic terms dominate in the early universe, which corresponds to the bouncing behavior of the universe to avoid initial singularity [27].…”
Section: Nonlinear Electrodynamics and General Equationsmentioning
confidence: 99%
“…In order to fulfill the requirement of isotropic and homogeneous universe, i.e., the electromagnetic field to act as its source, the energy density and the pressure corresponding to the electromagnetic field can be computed by averaging over volume [26,28]. It is assumed that the electric and magnetic fields have coherent lengths that are much shorter than the cosmological horizon scales.…”
Section: Nonlinear Electrodynamics and General Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nashed (2011) constructed regular charged spherically symmetric solutions with NLED coupled to teleparallel theory of gravity. Bandyopadhyay and Debnath (2011) considered a universe with magnetic field and matter in NLED and checked the validity of GSLT for magnetic universe bounded by Hubble, apparent, particle and event horizons. They concluded that the GSLT violates initially but holds for later times.…”
Section: Introductionmentioning
confidence: 99%